Black Country stories - Parr, Martin 1952- (Dewi Lewis Publishing, 2014)
A four-year project documenting everyday life in the Black Country comes to an end this year as renowned Magnum photographer, Martin Parr completes his work on Black Country Stories, which will be showcased at The New Art Gallery Walsall, opening on 4 October, 2014